2011
DOI: 10.7150/jca.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Prognostic Factors in an Observational Setting in Patients with Advanced Non-Small Cell Lung Carcinoma

Abstract: Background: This prospective observational study estimated the effect of prognostic factors, particularly continued smoking during therapy, on survival in advanced non-small cell lung cancer (NSCLC) patients receiving gemcitabine-platinum. Further, prognostic factors were used to build a survival model to improve prognosis prediction in naturalistic clinical settings.Methods: Eligibility criteria included: Stage IIIB/IV NSCLC, no prior chemotherapy, and Eastern Cooperative Oncology Group (ECOG) performance sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
12
2
Order By: Relevance
“…A positive link between smoking and unfavorable survival in lung cancer patients was noted in a large number of previous studies, although there is some controversy regarding this finding . In our study, current and former smokers exhibited a shorter survival compared with never smokers, but the results were not statistically significant (Supporting Information Table S2).…”
Section: Discussioncontrasting
confidence: 60%
“…A positive link between smoking and unfavorable survival in lung cancer patients was noted in a large number of previous studies, although there is some controversy regarding this finding . In our study, current and former smokers exhibited a shorter survival compared with never smokers, but the results were not statistically significant (Supporting Information Table S2).…”
Section: Discussioncontrasting
confidence: 60%
“…This finding is compatible with our results. On the other hand, Li et al reported that N staging was not an independent prognostic factor in 1214 advanced NSCLC patients who received gemcitabine in combination with platinum, although disease stage (stage IIIB or IV), PS, gemcitabine-platinum regimen, and T stage were independent predictors of survival [19]. This discrepancy may be due to the fact that the study included both stage IIIB and stage IV patients while our study registered only stage IV patients.…”
Section: Discussioncontrasting
confidence: 65%
“…Despite chemotherapy and radiotherapy, prognosis of advanced NSCLC patients remains very poor, with the 1-, 3- and 5-year survival rates for stage III NCSLC being 54, 24 and 13%, respectively [2]. While factors such as age, clinical stage and treatment methods have been suggested as potential prognosis factors [3,4], it remains difficult to predict the survival of advanced NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%